2019
DOI: 10.1167/iovs.19-27389
|View full text |Cite
|
Sign up to set email alerts
|

Increased Optic Nerve Head Capillary Blood Flow in Early Primary Open-Angle Glaucoma

Abstract: PURPOSE. Blood flow in the optic nerve head (ONH) is known to be reduced in eyes with advanced glaucoma. However, experimental results from non-human primates suggest an initial increase in ONH blood flow at the earliest stages of damage. This study assesses flow and pulsatile hemodynamics across a range of severities to test the hypothesis that this also occurs in human glaucoma. METHODS. Laser speckle flowgraphy was used to measure average mean blur rate (MBR ave) within ONH tissue (a correlate of capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…It is well known that a greater β-PPA area is a risk for progression of glaucoma 37 , 38 , being associated with the extent of glaucomatous visual field damage 39 41 . Therefore, lower MT-Skew associated with a greater β-PPA area seems compatible with an increase in glaucomatous damage or risk for glaucoma, and also with the previous results of lower MT-Skew reported in NTG 24 and POAG 26 . It is possible that after adjustment for age, DBP, and HR, MT-Skew could reflect circulatory changes in the ONH tissue associated with the β-PPA area.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is well known that a greater β-PPA area is a risk for progression of glaucoma 37 , 38 , being associated with the extent of glaucomatous visual field damage 39 41 . Therefore, lower MT-Skew associated with a greater β-PPA area seems compatible with an increase in glaucomatous damage or risk for glaucoma, and also with the previous results of lower MT-Skew reported in NTG 24 and POAG 26 . It is possible that after adjustment for age, DBP, and HR, MT-Skew could reflect circulatory changes in the ONH tissue associated with the β-PPA area.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the correlation to ocular factors, we found that the MT-Skew was significantly negatively correlated with the β-PPA area (Table 4 ). In previous reports, MT-Skew was significantly lower in patients with normal-tension glaucoma (NTG) 24 and primary open-angle glaucoma (POAG) 26 than in those with normal eyes. It is well known that a greater β-PPA area is a risk for progression of glaucoma 37 , 38 , being associated with the extent of glaucomatous visual field damage 39 41 .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations